1993
DOI: 10.1007/bf00132179
|View full text |Cite
|
Sign up to set email alerts
|

Changes in morphological and functional characteristics of male rat EDL muscle during growth

Abstract: Morphological and functional changes as well as changes in fibre-type composition were investigated in the left extensor digitorum longus (EDL) muscles of male Wistar rats of approximately 40, 60, 120 and 700 days old. A number of morphological changes occurred in the EDL muscle during growth. While from 40 to 120 days muscle mass and cross-sectional area (CSA) increased by 247 and 192%, changes in muscle and fibre lengths were much smaller (44 and 17%, respectively). Besides morphological changes tetanic forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Our finding of reduced max CaF/skinned fibre CSA in muscle fibres from rats in the early rapid growth phase (4-weeks postnatal), but not in the late rapid growth phase (8-weeks postnatal), is in agreement with the in situ data of Lodder et al [36,37] who showed that the specific force of whole rat EDL muscle at 5-6 weeks was significantly lower (−29%) than at 8-9 weeks, while specific force at 8-9 weeks was not different from that at 17-18 weeks. These findings suggest that in rats aged less than ∼8 weeks, the number of force producing cross-bridges per half sarcomere and/or the magnitude of force produced per cross-bridge are lower than in more mature rats.…”
Section: Specific Forcesupporting
confidence: 94%
See 2 more Smart Citations
“…Our finding of reduced max CaF/skinned fibre CSA in muscle fibres from rats in the early rapid growth phase (4-weeks postnatal), but not in the late rapid growth phase (8-weeks postnatal), is in agreement with the in situ data of Lodder et al [36,37] who showed that the specific force of whole rat EDL muscle at 5-6 weeks was significantly lower (−29%) than at 8-9 weeks, while specific force at 8-9 weeks was not different from that at 17-18 weeks. These findings suggest that in rats aged less than ∼8 weeks, the number of force producing cross-bridges per half sarcomere and/or the magnitude of force produced per cross-bridge are lower than in more mature rats.…”
Section: Specific Forcesupporting
confidence: 94%
“…In particular, these studies showed that the specific force (tetanic force/cross-sectional area) of the EDL was approximately 29% lower in rats aged 40 days (5-6 weeks) than in those aged 60 days (8-9 weeks) and 120 days (17-18 weeks). This disparity was not associated with age-related differences in fibre type composition, fibre number or fibre density leading the authors to speculate that there is an intrinsically lower force producing capability in rapidly growing rats compared to adult rats [36]. In a follow up study, Lodder et al [37] found that EDL muscles from rats aged 40 days were more fatigable than those of rats aged 60 and 120 days.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lodder et al (1993) evaluated the physiological importance of changes in MHC‐2b as fast‐fiber subtypes in the muscle composition, and suggested the association between changes in these isoforms and the contraction rate. He reported that the contraction rate is closely related to the composition of the MHC, and type 2b fibers are faster than type 2a fibers ( Bottinelli et al ., 1991 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in experiments aimed at studying the capacity of skeletal muscles to sustain a high isometric force during one continuous contraction or a series of repetitive contractions, stimulation frequencies are used which are lower than necessary to obtain maximal isometric force (e.g. de Haan, Jones & Sargeant, 1989;Lodder, de Haan, Lind & Sargeant, 1993). By using lower frequencies loss of force-generating capability due to activation failure can be prevented (Jones, Bigland-Ritchie & Edwards, 1979).…”
Section: Introductionmentioning
confidence: 99%